The Influence of Risk Management and Growth Strategies on Financial Performance - Rahma Wiyanti; Siti Hailatul Fikriyah (Universitas Pamulang, 2022)
This research examines risk management and growth strategies on the performance of financial the banks are listed on the Indonesia Stock Exchange. The general research objective is to ascertain the effect of risk management and growth strategies on the optimal performance of financial the Indonesian banks. Credit risk management is considered to play a role in minimizing the emergence of bad loans because bank loans have the aim of increasing profits and have triggered the emergence of bad loans in Indonesian banks due to improper management. It is hoped that this research will help improve bank viability, and risk management expected to reduce unemployment, as well as help, prevent the social evils that accompany it. This study uses financial performance as measured by ROA, risk management uses ratio to measure credit risk by Non-Performing Loans (NPL) and the bank’s performance ratio to assess bank liquidity in meeting the needs of funds withdrawn by the public in the form of deposits, saving or demand deposits is Loan to Deposit Ratio (LDR) as well as growth strategies. The company's growth strategies are one of the managerial efforts to increase the company's competitive position in the industry. The growth strategies are measured by revenue growth expressed as a percentage. This study uses secondary data, so all data needs are obtained from relevant secondary sources. This test has a sample data of 110 sample data for 5 periods. The technique of analysis used is multiple linear regression using the eViews-9 program. The results showed that risk management as proxied by NPL and LDR as well as growth strategies simultaneously affected financial performance. While partially NPL and sales growth have an impact on financial performance. Meanwhile, LDR has no effect on financial performance.